Does a Medial Retraction Blade Transmit Direct Pressure to Pharyngeal/Esophageal Wall During Anterior Cervical Surgery?. Issue 1 (1st January 2015) - Han, In Ho; Lee, Su Heon; Lee, Jae Min; Kim, Hwan Soo; Nam, Kyoung Hyup; Duetzmann, Stephan; Park, Jon; Choi, Byung Kwan
Abstract : Study Design: A prospective study of 25 patients who underwent anterior cervical surgery. Objective: To assess retraction pressure and the exposure of pharyngeal/esophageal (P/E) wall to the medial retractor blade to clarify whether medial retraction causes direct pressure transmission to the P/E wall. Summary of Background Data: Retraction pressure on P/E walls has been used to explain the relation between the retraction pressure and dysphagia or the efficacies of new retractor blades. However, it is doubtful whether the measured pressure represent real retraction pressure on the P/E wall because exposure of the P/E in the surgical field could be reduced by the shielding effect of thyroid cartilage. Methods: Epi- and endoesophageal pressures were serially measured using online pressure transducers 15 minutes before retraction, immediately after retraction, and 30 minutes after retraction. To measure the extent of P/E wall exposure to pressure transducer, we used posterior border of thyroid cartilage as a landmark. Intraoperative radiograph was used to mark the position of the posterior border of thyroid cartilage. We checked out the marked location on retractors by measuring the distance from distal retractor tip. Results: The mean epiesophageal pressure significantly increased after retraction (0 mmHg: 88.7 ± 19.6 mmHg: 81.9 ± 15.3 mmHg). The mean endoesophageal pressure minimally changed after retraction (9.0 ± 6.6 mmHg: 15.7 ± 13.8 mmHg: 17.0 ± 14.3 mmHg). The mean location of the posterior border of thyroid cartilage was 7.3 ± 3.5 mm on the retractor blade from the tip, which means epiesophageal pressure was measured against the posterior border of thyroid cartilage, not against the P/E wall. Conclusion: We suggest that a medial retraction blade does not transmit direct pressure on P/E wall due to minimal wall exposure and intervening thyroid cartilage. Our result should be considered when measuring retraction pressure during anterior cervical surgery or designing novel retractor systems. Level of Evidence: 2 Abstract : Endoesophageal pressure changed minimally as compared with epiesophageal pressure after retraction. Pharyngeal/esophageal wall exposure in the surgical field to medial retraction blades is minimal during anterior cervical surgery. The study shows that medial retraction blade cannot transmit direct pressure to the pharyngeal/esophageal wall during anterior cervical surgery.